PAR2 (Protease-Activated Receptor 2) Deficiency Attenuates Atherosclerosis in Mice. Issue 6 (June 2018) - Jones, Shannon M.; Mann, Adrien; Conrad, Kelsey; Saum, Keith; Hall, David E.; McKinney, Lisa M.; Robbins, Nathan; Thompson, Joel; Peairs, Abigail D.; Camerer, Eric; Rayner, Katey J.; Tranter, Michael; et al.
Abstract : Objective—: PAR2 (protease-activated receptor 2)-dependent signaling results in augmented inflammation and has been implicated in the pathogenesis of several autoimmune conditions. The objective of this study was to determine the effect of PAR2 deficiency on the development of atherosclerosis. Approach and Results—: PAR2 mRNA and protein expression is increased in human carotid artery and mouse aortic arch atheroma versus control carotid and aortic arch arteries, respectively. To determine the effect of PAR2 deficiency on atherosclerosis, male and female low-density lipoprotein receptor–deficient ( Ldlr −/− ) mice (8–12 weeks old) that were Par2 +/+ or Par2 −/− were fed a fat- and cholesterol-enriched diet for 12 or 24 weeks. PAR2 deficiency attenuated atherosclerosis in the aortic sinus and aortic root after 12 and 24 weeks. PAR2 deficiency did not alter total plasma cholesterol concentrations or lipoprotein distributions. Bone marrow transplantation showed that PAR2 on nonhematopoietic cells contributed to atherosclerosis. PAR2 deficiency significantly attenuated levels of the chemokines Ccl2 and Cxcl1 in the circulation and macrophage content in atherosclerotic lesions. Mechanistic studies using isolated primary vascular smooth muscle cells showed that PAR2 deficiency is associated with reduced Ccl2 and Cxcl1 mRNA expression and protein release into the supernatant resulting in less monocyte migration. Conclusions—: Our results indicate that PAR2 deficiency is associated with attenuation of atherosclerosis and may reduce lesion progression by blunting Ccl2 - and Cxcl1 -induced monocyte infiltration. Abstract : Supplemental Digital Content is available in the text.